Training Course On Geothermal Electricity - Potsdam - Schütz, Felina; Spalek, Angela (Zenodo, 2013)
Session I – Market aspects - C. Karytsas and D. Mendrinos Session II – Legal, environmental and financial aspects - S. Fraser, F. Jaudin and T. Reif Session III – Geothermal exploration and resource assessment - A. Manzella, J.‐D. van Wees, P. Durst and C. Dezayes Session IV – EGS technology - J.‐D. van Wees, G. Zimmermann, P. Durst and C. Dezayes Session V – Drilling - W. Brandt Session VI – Flash steam and binary technology - E. Hallgrímsdóttir and P. Bombarda Session VII – Plant operation, energy supply and grid integration - F. Heilemann and S. Reith : GEOELEC - IEE : {"references": ["Calcagno P., Bouchot V., Thinon I., Bourgine B., 2012. A New 3D Fault Model of the Bouillante Geothermal Province Combining Onshore and Offshore Structural Knowledge (French West Indies), Tectonophysics 526\u2010529 (2012) 185\u2010195.", "Genter A., Guillou\u2010Frottier L., Feybesse J.\u2010L., Nicol N., Dezayes C., Schwartz S., 2003. Typology of potential Hot Fractured Rock resources in Europe. Geothermics 23, p. 701\u2010710.", "Oskooi, B., Pedersen, L.B., Smirnov, M., \u00c1rnason, K., Eysteinsson, H., Manzella, A., and the DGP Working Group: The deep geothermal structure of the Mid\u2010Atlantic Ridge deduced from MT data in SW Iceland. Phys. Earth Planet. Int., 150, 183\u2010195, 2005.", "Spichak V., and Manzella A.: Electromagnetic sounding of geothermal zones, Journal of Applied Geophysics, 68, 459\u2013478, 2009. doi: 10.1016/j.jappgeo.2008.05.007.", "Cloetingh, S., Van Wees, J.D., Ziegler, P.,Lenkey, L., Beekman, F., Tesauro, M., Forster, A., Norden, B., Kaban, M., Hardebol, N., Bonte, D., Genter, A., Guillou\u2010Frottier, L., Voorde, M.T., Sokoutis, D., Willingshofer, E., Cornu, T., Worum, G., 2010. Lithosphere tectonics and thermo\u2010mechanical properties: an integrated modelling approach for Enhanced Geothermal Systems exploration in Europe. Earth\u2010Science Reviews 102, 159\u2010206.", "Bruhn, D., Huenges, E, Agustsson, K, Zang, A, , Rachez, X., Wiemer, S., Van Wees,.J,D..Calcagno, P., , 2011. Geothermal Engineering Integrating Mitigation of Induced Seismicity in Reservoirs \u2010 The European GEISER Project. GRC transactions, 39.", "Wassing, B., Van Wees, J.D., Fokker, P., 2012. , Coupled Continuum Modeling of Fracture Reactivation and Induced Seismicity During Enhanced Geothermal Operations. ARMA paper 12\u2010400.", "Zimmermann, G. Bl\u00f6cher, G. Reinicke, A Brandt, W. (2011): Rock specific hydraulic fracturing and matrix acidizing to enhance a geothermal system \u2010 Concepts and field results. Tectonophysics, 503, 1\u20102, 146\u2010154.", "Zimmermann, G; Moeck, I. Bl\u00f6cher, G. (2010): Cyclic waterfrac stimulation to develop an enhanced geothermal system (EGS): Conceptual design and experimental results.. Geothermics, 39, 1, 59\u201069.", "Zimmermann, G. Reinicke, A. (2010): Hydraulic stimulation of a deep sandstone reservoir to develop an Enhanced Geothermal System: Laboratory and field experiments. Geothermics, 39, 1, 70\u201077.", "Dezayes C., Genter A., Valley B., 2010. Overview of the Fracture Network at Different Scales Within the Granite Reservoir of the EGS Soultz Site (Alsace, France), Proceedings World Geothermal Congress 2010, Bali, Indonesia.", "Genter A., Evans K., Cuenot N., Baticci F., Dorbath L., Graff J.\u2010J. Sanjuan B., 2009. The EGS Soultz Project (France): From Reservoir Development to Electricity Production, GRC Transactions, Geothermal Resources Council (GRC) Annual Meeting 2009, Reno, USA.", "Ungemach, P., Antics, M., 2012 Geothermal well drilling. Sch\u00fctz, F. and A. Spalek (eds.), in Manual of the First Training Course on Geothermal Energy, 5\u20109 November 2012, Strasbourg, France, pp. 12\u201017.", "Tischner et al., 2006 Hot Dry Rock Projekt Soultz: Erste Phase der Erstellung einer wissenschaftlichen Pilotanlage, Abschlussbericht, BGR und BESTC GmbH 2006.", "Barker 1998, quoted in Sperber,A., Moeck, I.; Brandt, W. Drilling into Geothermal reservoirs. Huenges,E. (ed.) Geothermal Energy Systems Exploration, Development, and Utilization, Wiley\u2010VCH Verlag GmbH&Co. KGaA, Weinheim 2010.", "Oppelt, J. Geothermie und innovative Bohrtechnik. Vortrag Geozentrum Hannover Geothermietag 30. Oktober 2008. http://www.sjvgeology.org/history/gushers_world.html.", "Hallgr\u00edmsd\u00f3ttir E., Ballzus C. and Hr\u00f3lfsson H. (2012); \"The Hellishei\u00f0i Power Plant, Iceland.\" GRC transaction, Volume 36, page 1067 \u0336 1072.", "Angelino G., Bini R., Bombarda P., Gaia M., Girardi P., Lucchi P., Macchi E., Rognoni M., Sabatelli F., \"One MW binary cycle turbogenerator module made in Europe\", \" World Geothermal Congress\", Firenze, 1995.", "Bombarda, P., Duvia, A., Macchi, E., \"Combined, Mixed and Binary cycles for electricity Generation from Geothermal Sources \u2010 part A: selected configurations and calculation model\", Proceedings of \"The 20th New Zealand Geothermal Workshop\", pp. 347\u2010352, \", Geothermal Institute, The University of Auckland, 1998, Nuova Zelanda ISBN 0\u201086869\u2010083\u2010X.", "Bombarda, P., \"Combined, Mixed and Binary cycles for electricity Generation from Geothermal Sources \u2010 part B: technical economic analysis \", Proceedings of \"The 20th New Zealand Geothermal Workshop\", pp. 353\u2010358, Geothermal Institute, The University of Auckland, 11\u201013 novembre 1998, Nuova Zelanda ISBN 0\u201086869\u2010083\u2010X. \"Best Engineering Paper\".", "Bombarda, P. Macchi, E., \"Optimum cycle for geothermal power plants\", Proceedings of the \"World Geothermal Congress 2000\", pag. 3133\u20103138, Tokyo 2000.", "Bombarda, P., Gaia M., \"Binary Systems with Geothermal Fluid Pressurization to Avoid Flashing: Energy Evaluation of Down\u2010Hole Pump Cooling Below Geothermal Fluid Temperature\" Proceedings of the \"World Geothermal Congress 2005, Antalya, Turchia, 2005.", "Bombarda, P., Gaia M., \"Geothermal Binary Plants Utilising an Innovative Non\u2010Flammable Azeotropic Mixture as Working Fluid\" Proceedings of 28th NZ Geothermal Workshop \u2010 New Zealand, novembre 2006.", "Bombarda, P., Gaia, M., Pietra, C., \"Integration of Geothermal Liquid Dominated Sources and Waste Heat Sources for Electricity Production\", Proceedings of the \"World Geothermal Congress 2010, Bali, Indonesia.", "BDEW. (2012). Ermittlung von Entsch\u00e4digungszahlungen nach \u00a7 12 Abs. 1 EEG 2009. Berlin: Bund deutscher Energiewirtschaft.", "BDEW. (2008). Technische Richtlinien Erzeugungsanlagen am Mittelspannungsnetz \u2010 Richtlinien f\u00fcr Anschluss und Paralellbetrieb von Erzeugungsanlagen am Mittelspannungsnetz. Berlin: Bund deutscher Energiewirtschaft.", "BMU. (2011, December 14). Rechtsquellen erneuerbare Energien. Retrieved September 28, 2012, from http://www.res\u2010legal.de/suche\u2010nach\u2010laendern/frankreich/mehr\u2010zum\u2010thema/land/frankreich/ueberblick/foerderung.html", "BMWi. (2012). Energiedaten Deutschland. Berlin: Bundesministerium f\u00fcr Wirtschaft und Technolgie.", "BNetzA. (2011). Abschaltrangfolge, Berechnung der Entsch\u00e4digungszahlungen und Auswirkungen auf die Netzentgelte. Bonn: Federal Network Agency.", "BRD. (2012). Erneurebare Energien Gesetz (EEG). Berlin: Bundesrepublik Deutschland.", "BRD. (1990). Gesetz \u00fcber die Einspeisung von Strom aus erneuerbaren Energien in das \u00f6ffentliche Netz . Bonn: Bundesrepublik Deutschland.", "European Commission. (2012, September 10). Climate Action \u2010 The EU Climate and Energy Package. Retrieved September 27, 2012, from: http://ec.europa.eu/clima/policies/package/index_en.htm", "European Parliament and the Council. (2003). EU \u2010 Directive 2003/54/EC. Brussels: European Parliament and the Council.", "Geothermie Bundesverband. (n.d.). Geothermie in Zahlen. Retrieved October 05, 2012, from http://www.geothermie.de/aktuelles/geothermie\u2010in\u2010zahlen.html", "Konstantin, P. (2007). Praxisbuch Energiewirtschaft. Stuttgart: Springer Verlag.", "Paschen, H., Oertel, D., & Gr\u00fcnwald, R. (2003). M\u00f6glichkeiten geothermischer Stromerzeugung in Deutschland \u2010 Arbeitsbericht Nr. 84. Berlin: TAB B\u00fcro f\u00fcr Technikfolgen\u2010Absch\u00e4tzung beim Deutschen Bundestag.", "Tidball, R., Bluestein, J., Rodriguez, N., & Knoke, S. (2010). Cost and Performance Assumptions for Modeling Electricity Generation Technologies. Fairfax: National renewable energy laboratory.", "VDN. (2004). EEG\u2010Erzeugungsanlagen am Hoch\u2010 und Mittelspannungsnetz \u2010 Leitfaden f\u00fcr Anschluss und Paralellbetrieb von Erzeugungsanlagen auf Basis erneuerbarer Energien an das Hoch\u2010 und H\u00f6chstspannungsnetz. Berlin: Verband deutscher Netzbetreiber."]}